A study of women in top business roles: The case of the wine industry - Galbreath, Jeremy (2018)
Purpose – The purpose of this chapter is to empirically explore the extent to which women are advancing in the wine industry, and whether there are conditions which help facilitate their advancement. There is a perception that women are making great strides in the wine industry. However, this perception is largely anecdotal. Design/methodology/approach – All wineries in Australia are examined in each year for the years 2007 to 2013. By relying on a leading wine industry database, women in CEO, winemaker, viticulturist and marketing roles are examined. Findings – With the exception of the marketing role, women are underrepresented relative to predicted representation rates. Regarding regional differences, there is no consistent pattern with respect to where women representation in the roles is higher. The findings also suggest that where there is a woman CEO, women are more likely to be represented in winemaker, viticulturist and marketing roles. Research limitations/implications – The study represents Australian wine regions and should not be taken as a general population sample. The representation rates of women in top roles in other wine firms around the world may vary, which could lead to results different than those found in this study. Practical implications – For firms and policy makers interested in increasing the representation rates of women in the wine industry, the results of this study offer some insight into where current rates stand, and what might be underlying these representation rates. This is expected to facilitate debate around the means and mechanisms through which to increase the representation of women in the wine industry. Originality/value – This is the first known large-scale study to examine the representation rates of women in top roles in the wine industry; therefore, it offers both new insights and avenues for future research.